2019
DOI: 10.1037/pro0000272
|View full text |Cite
|
Sign up to set email alerts
|

Psychological assessment in abuse and neglect cases: The utility of the MMPI-2.

Abstract: The psychological assessment of parents involved in proceedings about their parental rights is often ordered by the Court in order to determine personality traits linked to potential problems in parental competences. We compared the Minnesota Multiphasic Personality Inventory (MMPI)-2 scores of this specific sample with a comparison group of parents involved in child custody litigations, considering a total of 429 individuals undergoing personality evaluations ordered by several Italian courts. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
7
2
Order By: Relevance
“…Moreover, they tend to take imprudent risks and may have problems related to alcohol or drug abuse (Nichols, 2011). In general, the MMPI‐2 findings are consistent with prior results in child custody literature (e.g., Roma et al, 2014; Carstairs et al, 2012) and in child abuse and neglect cases (Stredny et al, 2006; Ezzo et al, 2007; Resendes & Lecci, 2012; Gambetti et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Moreover, they tend to take imprudent risks and may have problems related to alcohol or drug abuse (Nichols, 2011). In general, the MMPI‐2 findings are consistent with prior results in child custody literature (e.g., Roma et al, 2014; Carstairs et al, 2012) and in child abuse and neglect cases (Stredny et al, 2006; Ezzo et al, 2007; Resendes & Lecci, 2012; Gambetti et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…As hypothesized (Hypothesis 1), this sample showed a defensive approach to assessment, common in a parental competency evaluation setting (Carr et al, 2005; Cooke, 2010; Roma et al, 2014; Gambetti et al, 2019), as shown by moderate range ( T‐scores = 55 to 65) elevations in the L (Lie) and TRIN (True Response Consistency Scale) scales of the MMPI‐2 and in the IM (Impression Management) scale of the 16PF‐5 (below the cut‐off point at the percentile score of 95, which corresponds to raw scores of 19 in females and 21 in males). In particular, they tended to respond in a socially desirable way, presenting themselves in a morally and culturally favorable light, over‐reporting “good behavior” or under‐reporting undesirable behavior (Cattell & Schuerger, 2003; Handel et al, 2006; Nichols, 2011).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations